Facilitating collaboration between Japanese high schools and universities: a qualitative exploration of the role of education outreach coordinators - Mori, Akiko (Frontiers in Education, 2024)
In recent years, universities have been expected to participate in Japanese high school education, especially in the "period for inquiry-based cross-disciplinary study." Despite various university faculties engaging in diverse educational practices, there is insufficient research on human resource development and the creation of mechanisms to ensure continuous development.This study conducted semi-structured interviews from July to November 2023, with 15 educators from universities and high schools, among others, to explore the current state of educational collaborations between these institutions and identify potential solutions.A reflective thematic analysis of the interview identified two key themes: the significance of university involvement in high school education and conflict areas generated from this collaboration. The findings suggest that the success of these initiatives relies on the involvement of coordinators who possess a high level of expertise and competencies.Discussion: These coordinators, who work in the "third space" in universities, are crucial for realizing the ideal outcomes of educational collaborations between universities and high schools in Japan's new educational environment.In the Japanese education system, particularly at the high school level, there is an increasing expectation for more university involvement.